ANALISIS JANGKAUAN FASILITAS KESEHATAN DI KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Dita Kurnia; Afdhal Afdhal (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to determine the range of service for health facilities in the form of hospitals, health centers and sub-health centers in Lubuk Basung District, Agam Regency. This study uses a quantitative approach with a descriptive method. The location of the research was carried out in Lubuk Basung District. The population of this research is health facilities in Lubuk Basung District with a total of 1 hospital, 2 health centers, and 13 sub-health centers. The data analysis technique used is buffer analysis to determine the reach of health facilities with service range of 10 km for hospital, 3 km for health centers and 1,5 km for sub-health center. The result showed that Lubuk Basung District with 1 hospital, 2 health center, and 13 sub-healh center were able to serve the entire community well.